Fermented Sugar From Ultrasound-Assisted Acid Hydrolysis Berenuk Fruit (Crecentia Cujete L.) - Nita Indriyani; Lusiana Lumbantoruan; Ummu Musfika; F. Fathurrahman (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2024)
Berenuk fruit (Crecentia Cujete L) is a non-food plant often found in tropical areas. Berenuk has quite a high content of carbohydrates and its derivatives. Among them are 18.61% carbohydrates, 59.86% sucrose, 25.09% fructose, and 18.24% galactose, so berenuk fruit has the potential to be a source or ingredient for bioethanol. The bioethanol process from biomass goes through several steps: raw material preparation, hydrolysis process and fermentation. The hydrolysis process is the process of breaking down carbohydrate into glucose units which are connected by Î²-1,4 glycosidic bonds. Another method of breaking sugar polymers can be done using alternative energy such as ultrasonic waves (50Hz, 50W) or microwaves. In this research, an ultrasonic-assisted acid hydrolysis process was carried out. The type of acid used is concentrated sulfuric acid (H2SO4). Ingredients ratio 1:20 (w/v) berenuk powder sample with sulfuric acid. The sulfuric acid concentrations used were 1 M, 2 M, and 3 M. Hydrolysis times were 40 minutes, 60 minutes, and 80 minutes at a temperature of 1000C. The results of research that has been carried out on the preparation process of bereneuk fruit have an average water content of 97.44%, so treatment is required before proceeding to the hydrolysis and fermentation process, namely by drying the drying process is carried out directly in sunlight for seven days, then continued by heating the oven for 8 hours at 1000C. In the ultrasonic wave assisted hydrolysis process carried out at a H2SO4 concentration of 3 M, a hydrolysis time of 80 minutes, and a temperature of 1000C produces 22.20% glucose.